Implementasi Sistem Informasi Manajemen Pegawai (Simpeg) Di Lembaga Pendidikan: Kajian Literatur - Yeni Sapitri; M. Din; Suarnida; Fitri Mayani; Surkana; Irwansyah Putra (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
Human Resources (HR) is the most crucial asset and main driver in determining the quality, effectiveness, and success of an educational institution. However, many educational institutions still rely on conventional, manual, and paper-based employee management systems, resulting in data redundancy, slow bureaucratic processes, and difficulty in making strategic decisions. The implementation of an Employee Management Information System (SIMPEG) offers a solution through a centralized, web-based digital platform that integrates employee data management, digital attendance, performance evaluation (SKP), and Employee Self-Service (ESS). This paper uses a qualitative descriptive method with a literature study approach to examine the concept, main functions, technical components, benefits, and challenges of SIMPEG implementation in educational institutions. The results show that SIMPEG significantly reduces operational costs, increases data accuracy through the Single Source of Truth (SSOT) concept, and accelerates decision-making. However, challenges such as digital culture resistance, infrastructure limitations, and regulatory misalignment with government systems (Dapodik/SISTER) need to be mitigated through intensive training, hybrid system development, and API integration. The conclusion confirms that SIMPEG is the main foundation for realizing modern, professional, and accountable educational institutions in the digital era.